Direito humano ao meio ambiente, vulnerabilidade e alterações ambientais: justiça geracional e deslocados ambientais - Souza, Karla Karolina Harada (2019)
This study aims to understand the environmental changes and environmental protection in the current risk society and Anthropocene Era. Initially, was addressed the human right to environment through an integrative vision, highlighting an interdependence with other human rights, observing the greening of human rights, in building a new sustainable and environmental ethics, through the prism of Jushumanism, integral humanism and solidarity. The understand environmental changes and the various layers and forms of vulnerability to demonstrate their relationship with human rights. Starting from the premise of the principle of sustainability, a dedicated study of justice theories, to bring foundation to generational justice (intergenerational justice and intragerational justice), and to understand the rights of the present and to present the benefits to tan ecologically balanced environment. Thus, in the context of environmental change, in a risky and globalized society, the present study seeks to investigate the existing protection for people who are in a situation of forced displacement (no choice option) because of environmental problems or changes in the environment. In this regard, using a rights based approach, searching to identify protection for environmentally displaced persons, both internally and internationally, using the framework and the existing structures, instruments, concepts, institutions and diplomas in international human rights law